The influence of AI adoption, research skills, and statistical knowledge on graduate students’ statistical productivity - Baluyos, Genelyn R.; Aclao, Joel Tapayan (Indonesian Journal of Curriculum and Educational Technology Studies, 2025)
Ensuring statistical productivity is essential for enhancing research efficiency and quality. This study examined the correlation between Artificial Intelligence (AI) adoption, research skills, and statistical knowledge with statistical productivity among graduate students in Misamis Occidental during the academic year 2023–2024. Employing a descriptive-correlational design, 192 graduate students were selected through stratified random sampling. Data were collected using researcher-developed questionnaires and analysed using mean, standard deviation, Pearson correlation, and stepwise multiple regression analysis. The findings indicated high levels of AI adoption, research skills, and statistical knowledge, all of which were positively correlated with statistical productivity. AI engagement, research proficiency, and statistical expertise were significant predictors of statistical productivity. Active use of AI and a strong understanding of statistical concepts notably enhanced students’ ability to analyse and interpret data. To further improve productivity, it is recommended that school administrators establish research centres equipped with appropriate software and tools to support research and statistical analysis.